2019
DOI: 10.1093/neuros/nyz500
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intra-Arterial Papaverine-Hydrochloride on Cerebral Metabolism and Oxygenation for Treatment of Delayed-Onset Post-Subarachnoid Hemorrhage Vasospasm

Abstract: BACKGROUND Delayed posthemorrhagic vasospasm remains among the major complications after aneurysmal subarachnoid hemorrhage (SAH) and can result in devastating ischemic strokes. As rescue therapy, neurointerventional procedures are used for selective vasodilatation. OBJECTIVE To investigate the effects of intra-arterial papaverine-hydrochloride on cerebral metabolism and oxygenation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The accuracy, sensitivity, and specificity of the XGBoost and logistic regression were calculated in Table 3. In the literature, there are studies that analyzed the data obtained to confirm the factors predicting a DCI [28][29][30][31]. A young age, aneurysm size, a large volume of SAH, poor neurologic grade on admission, smoking, HTN, and female gender were known as risk factors for vasospasm following aSAH [31,32].…”
Section: Performance Evaluation Using ML Modelingmentioning
confidence: 99%
“…The accuracy, sensitivity, and specificity of the XGBoost and logistic regression were calculated in Table 3. In the literature, there are studies that analyzed the data obtained to confirm the factors predicting a DCI [28][29][30][31]. A young age, aneurysm size, a large volume of SAH, poor neurologic grade on admission, smoking, HTN, and female gender were known as risk factors for vasospasm following aSAH [31,32].…”
Section: Performance Evaluation Using ML Modelingmentioning
confidence: 99%
“…Intrahospital transport, head elevation/flat position 3 (Burnol et al, 2021;Dagod et al, 2021;Hosmann et al, 2021) Vasospasm therapy Nimodipine, endovascular therapy, papaverinehydrochloride 4 ( Hockel et al, 2016;Albanna et al, 2017;Hockel et al, 2017;Hosmann et al, 2020) Ventilation management Hyperoxia, hypercapnia, hypocapnia 10 ( Westermaier et al, 2016;Zhang et al, 2016;Ghosh et al, 2017;Sahoo et al, 2017;Brandi et al, 2019;Calviello et al, 2019;Svedung Wettervik et al, 2020b;Stetter et al, 2021;Gargadennec et al, 2022;Hosmann et al, 2022) b Other therapies Analgesia, hypothermia, enteral nutrition, decompressive craniectomy 4 ( Flynn et al, 2015;Kofler et al, 2018;Kovac et al, 2018;Ianosi et al, 2020) a One study included both cerebral intervention and MMM-guided treatment (mixed interventions Frontiers in Physiology frontiersin.org (Svedung Wettervik et al, 2019;Svedung Wettervik et al, 2020b;Svedung Wettervik et al, 2020a). The strength of a recycled study cohort is that it saves time and money; and could result in a broad understanding of the neuromonitoring signals.…”
Section: Physical (Movement) Interventionsmentioning
confidence: 99%
“…While the use of CMD has shown to improve functional outcomes, including the reduced mortality rate and better Glasgow coma scales 3-6 months post-injury, in patients with traumatic brain injury [15], the relationship between the CMD monitoring and clinical outcomes in SAH patients remain to be elucidated. Also, it has been reported that CMD may help to assess the efficacy of SAH-related interventions [54,57]. Furthermore, despite a recent article proposing the standard CMD reporting recommendations [61], a more comprehensive meta-analysis might be required for further standardizing the reporting of CMD results from both clinical and experimental studies due to the current variability in reported data of CMD in the literature.…”
Section: Clinical Application Of Cmd In Sahmentioning
confidence: 99%